Intersubunit signaling in RecBCD enzyme, a complex protein machine regulated by Chi hot spots - Amundsen, Susan K. (Cold Spring Harbor Laboratory Press, 2007)
The Escherichia coli RecBCD helicase–nuclease, a paradigm of complex protein machines, initiates homologous genetic recombination and the repair of broken DNA. Starting at a duplex end, RecBCD unwinds DNA with its fast RecD helicase and slower RecB helicase on complementary strands. Upon encountering a Chi hot spot (5′-GCTGGTGG-3′), the enzyme produces a new 3′ single-strand end and loads RecA protein onto it, but how Chi regulates RecBCD is unknown. We report a new class of mutant RecBCD enzymes that cut DNA at novel positions that depend on the DNA substrate length and that are strictly correlated with the RecB:RecD helicase rates. We conclude that in the mutant enzymes when RecD reaches the DNA end, it signals RecB’s nuclease domain to cut the DNA. As predicted by this interpretation, the mutant enzymes cut closer to the entry point on DNA when unwinding is blocked by another RecBCD molecule traveling in the opposite direction. Furthermore, when RecD is slowed by a mutation altering its ATPase site such that RecB reaches the DNA end before RecD does, the length-dependent cuts are abolished. These observations lead us to hypothesize that, in wild-type RecBCD enzyme, Chi is recognized by RecC, which then signals RecD to stop, which in turn signals RecB to cut the DNA and load RecA. We discuss support for this “signal cascade” hypothesis and tests of it. Intersubunit signaling may regulate other complex protein machines.